THE EFFECT OF USING DIGITAL MIND MAPPING ON STUDENTS’ READING COMPREHENSION ABILITY AT SMPN 2 RAMBAH SAMO - Syifa Aulia; Fadly Azhar; Mahdum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using digital mind mapping on students' reading comprehension ability in recount texts. This study uses a pre-experimental method with one group pre-test post-test. The research sample consisted of eighth-grade students at SMPN 2 Rambah Samo in the 2025/2026 academic year. The research instrument was a multiple-choice test consisting of 32 questions that had been tested for validity and reliability (Cronbach's Alpha = 0.974). The data were analyzed using normality tests, paired sample t-tests, and N-Gain. The results showed an increase in students' reading comprehension skills after using digital mind maps. The average pre-test score was 58.93, while the post-test score was 67.36. The Sig. value (two tails) was 0.000 < 0.05, so Ha was accepted. Thus, digital mind maps have a significant effect on students' reading comprehension ability.